Manajemen Tata Kelola Kepariwisataan Berbasis Masyarakat Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toraja Utara - Layuk, Sofyan Patrich; Suyuthi, Nurmadhani Fitri; Rukaiyah, St (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the management of community-based tourism governance at the Department of Culture and Tourism of North Toraja Regency. The research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Informants include village heads, tourism managers, vendors, local communities, and visitors. The study focuses on planning, organizing, implementation, and supervision in community-based tourism management. The results indicate that community-based tourism management plays a crucial role in empowering the community, improving economic welfare, preserving the environment, and maintaining local culture. The success of this management is influenced by coordination among the government, business actors, communities, and academics through a structured and synergistic Destination Management Organization (DMO) concept. This study recommends enhancing active community participation and ensuring continuous planning and supervision to achieve inclusive and sustainable tourism.